Strategic Business Sustainability: A Comprehensive Risk Management Examination of SME Participation in Maritime Events Pinisi Festival - Surya Dewi; Syafruddin Syafruddin (Newinera Publisher, 2024)
The Pinisi Festival in Bulukumba, Indonesia, showcases the cultural heritage of the Kajang community and offers a platform for Micro, Small, and Medium Enterprises (MSMEs) to participate and benefit from the tourism sector. This study examines the role of effective risk management in enhancing the sustainability of MSME participation in the festival. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and document analysis. Findings reveal that MSMEs demonstrate a good understanding of risk management, identifying key risks such as damage to goods, a decrease in visitor numbers, and adverse weather conditions. To mitigate these risks, MSMEs employ strategies such as maintaining backup stock, intensifying marketing efforts, and investing in weather-resistant infrastructure. The application of effective risk management not only helps MSMEs address challenges during the festival but also enhances their competitiveness in the market. Furthermore, government support and collaboration with private entities play a crucial role in overcoming challenges and ensuring the success of the festival. This study contributes to the understanding of risk management practices in MSMEs and highlights the importance of collaboration in promoting sustainable tourism development.